The Influence of Work Discipline And Work Environment on Motivation That Has an Impact on Employee Productivity at PT. Argo Textile in Tangerang - Sri Mulyani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to determine the effect of work discipline and work environment on motivation, impacting employee productivity at PT. Argo Textile in Tangerang. The method used is explanatory research with a sample of 125 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study, work discipline has a significant effect on motivation by 41.4%, hypothesis testing obtained a significance of 0.000 <0.05. Furthermore, the work environment significantly affects motivation by 36.1%; hypothesis testing acquired a value of 0.000 <0.05. Finally, work discipline and work environment simultaneously significantly affect motivation by 51.0%; hypothesis testing obtained a significance of 0.000 <0.05.